MARKETING ANALYSIS OF DUCK EGGS IN PUURODA VILLAGE, BAULA DISTRICT, KOLAKA REGENCY - Campina Illa Prihantini; Dewi Yulan Dari; Nurhaliza Nurhaliza; Herdiansyah Herdiansyah; Nirma Nirma; Asharil Yaqub (AGROLAND The Agricultural Sciences Journal (e-Journal), 2021)
This study aimed to determine the channel and efficiency of marketing duck eggs in Puuroda Village, Baula District, Kolaka Regency. The research and data collection methods were surveys, observations, and interviews using a questionnaire. There are three marketing channels for duck eggs in Puuroda Village, Baula District, Kolaka Regency. Based on the farmer's share analysis results, the highest is retailer marketing channel I, with a farmer's share value of 100%. In contrast, the lowest is in marketing channel III, with a farmer share value of 71.42%. Based on the study results, it is recommended to lay duck breeders in Puuroda Village, Baula District, Kolaka Regency to sell duck eggs directly to consumers or directly to duck egg retailers.